1992
DOI: 10.1016/0735-1097(92)90480-b
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage in association with thrombolytic therapy: Incidence and clinical predictive factors

Abstract: In a period of 18 months, 2,469 patients with acute myocardial infarction treated with a thrombolytic agent were prospectively registered in 61 hospitals. Most patients (73%) were treated with streptokinase. Intracranial hemorrhage was observed in 24 patients, corresponding to an incidence rate of 1% (95% confidence interval 0.6% to 1.3%). The median time interval between the start of thrombolytic therapy and the first clinical signs of intracranial bleeding was 16 h (range 3 to 36). In total, 16 (66%) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(29 citation statements)
references
References 33 publications
2
25
0
2
Order By: Relevance
“…Although a similar finding was reported in MI patients by Bovill et al, 10 Califf et al, 22 and DeJaegere et al, 15 the failure in these MI studies to base TPA dose on body weight or surface area leaves open the possibility that greater bleeding in lighter patients seen in those studies could simply have been a dose effect. In contrast, our data support the possibility that lighter patients may have a greater risk of bleeding independent of the TPA dose used.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Although a similar finding was reported in MI patients by Bovill et al, 10 Califf et al, 22 and DeJaegere et al, 15 the failure in these MI studies to base TPA dose on body weight or surface area leaves open the possibility that greater bleeding in lighter patients seen in those studies could simply have been a dose effect. In contrast, our data support the possibility that lighter patients may have a greater risk of bleeding independent of the TPA dose used.…”
Section: Discussionmentioning
confidence: 42%
“…DeJaegere et al 15 performed a case-control study of MI patients in the Netherlands who had intracranial hemorrhages while being treated with thrombolytic agents. Patients with a body weight less than 70 kg were nearly four times more likely to have an intracranial hemorrhage than heavier patients.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have not had sufficient power to achieve statistical significance despite at least 1 study with a suggestive trend. 25 Because excessive anticoagulation with warfarin is strongly and consistently related to intracranial hemorrhage and because it is specifically mentioned as a relative contraindication in national guidelines, we believed that its inclusion in the scale was justified.…”
Section: Brass Et Almentioning
confidence: 99%
“…7,35,38,43 Recommendation for weight-based dosing became widespread several years before the start of this study, based on results such as the TIMI-II. 29 A lower body weight may result in higher serum concentration of medication, resulting in a greater degree of fibrinolytic activity 25 and an increased risk for hemorrhage. It has been suggested that this effect may be seen with TPA but not streptokinase.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation